2014
DOI: 10.1037/a0037183
|View full text |Cite
|
Sign up to set email alerts
|

The role of mindfulness and psychological capital on the well-being of leaders.

Abstract: In today’s highly competitive and extremely complex global economy, organizational leaders at all levels are facing unprecedented challenges. Yet, some seem to be handling the pressure better than others. Utilizing 4 samples of CEOs/presidents/top (n = 205), middle (n = 183), and junior (n = 202) managers, as well as 107 entrepreneurs, using Structural Equation Modeling we tested the direct effect that their level of mindfulness (heightened awareness) and the mediating effect of their psychological capital (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
267
4
12

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(300 citation statements)
references
References 93 publications
(183 reference statements)
17
267
4
12
Order By: Relevance
“…We found that the higher the qualifications, the higher the PsyCap values, namely: self-efficacy, resilience and hope, which allows us to partially corroborate the third hypothesis. In agreement with Luthans et al (2014), self-efficacy operates as a basis of positivity, so the bigger the capacity to mobilize the cognitive resources and the necessary actions for a well succeeded performance, the more confident people feel, trying harder to make positive choices. In the same line, Cunha et al (2008) defend that the more people adjust to the functions they perform and the better the knowledge about people they have, the more effort they make to reach their goals and better adapt to situations that cause psychic suffering.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that the higher the qualifications, the higher the PsyCap values, namely: self-efficacy, resilience and hope, which allows us to partially corroborate the third hypothesis. In agreement with Luthans et al (2014), self-efficacy operates as a basis of positivity, so the bigger the capacity to mobilize the cognitive resources and the necessary actions for a well succeeded performance, the more confident people feel, trying harder to make positive choices. In the same line, Cunha et al (2008) defend that the more people adjust to the functions they perform and the better the knowledge about people they have, the more effort they make to reach their goals and better adapt to situations that cause psychic suffering.…”
Section: Resultsmentioning
confidence: 90%
“…Discussion Roche, Haar, and Luthans (2014) suggested that the findings of positive psychology contribute to improve individual and collective functioning and promote psychological well-being. Positive experiences strengthen minds and shape behaviours because they prepare people for day-to-day adversities and stimulate the boldness required to tackle problems.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest mindfulness to be positively related to job satisfaction (Hülsheger et al, 2013;Dane & Brummer, 2014), job engagement (Leroy et al, 2013), job performance (Shonin et al, 2014b;Andrews, Kacmar & Kacmar, 2014) and work-related well-being (Shonin et al, 2014b;Roche, Haar & Luthans 2014), and negatively related to emotional issues (Hülsheger et al, 2013;Roche, Haar & Luthans 2014;Shonin et al, 2014b) and turnover intentions (Dane & Brummer, 2014;Andrews, Kacmar & Kacmar, 2014).…”
Section: Organizational Challenges and Mindfulness Researchmentioning
confidence: 99%
“…Two online studies suggested mindfulness to be positively related to job engagement, job performance (Andrews, Kacmar & Kacmar, 2014) and job satisfaction (Dane & Brummer, 2014) and negatively related to turnover intentions (possibility that an individual would leave the organization) (Andrews, Kacmar & Kacmar, 2014;Dane & Brummer, 2014). Roche, Haar & Luthans (2014) examined the effect of level of mindfulness (MAAS) on psychological well-being in a sample of top (N = 205), middle (N = 183) and junior (N = 202) managers, and also 107 entrepreneurs. Mindfulness was negatively related to anxiety, depression and had a negative effect in the case of managerial leaders, and to burnout in the case of entrepreneurs.…”
Section: Mindfulness-based Interventions On Workplacementioning
confidence: 99%
See 1 more Smart Citation